Synthesis and Antimicrobial Evaluation of Some Nitro-Mannich Bases Derived from β-Nitrostyrene - Mardia Telep El-Sayed; Eman Kishk; El-Sayed Afsah (Open Journal of Chemistry - Peertechz Publications, 2015)
The present work focused on exploring the reactivity of β-nitrostyrene towards Mannich reaction with different approaches. The synthesized nitro-Mannich bases were tested as antimicrobial agents that showed high activity against both gram positive and gram negative bacteria.